Innovation Process Adjusting in Peripheral Regions. The Case of Podlaskie Voivodship - Ciborowski, Robert (Equilibrium. Equilibrium. Quarterly Journal of Economics and Economic Policy, 2014)
Comparative studies indicate that innovation activity in Poland is, in general, significantly below that of EU and in North-east it is below that of other parts of Poland. There is peripheral region with traditional structure of production and employment. The North-east remains one of the least innovative regions of Poland and enlarged EU. This is probably the result of the obsolete institutional setting, which doesn’t reflect the requirements of modern international competitiveness. It is the heritage of past times, where creation of the innovation system wasn’t considered a priority factor of economic development. Additionally, Poland is still undergoing intensive modernization of its technology capabilities. The capital and production structure are way outdated and don’t meet the demands of the international trade competition, most of all the non-price competition. That is why it seems that creating conditions for innovation system might become a crucial factors determining the nature and dynamics of development processes as well as influencing the North-east future innovation capability. Creating a new regional innovation structure and transfer of technologies should support modernization processes in companies and the creation of development opportunities for the national economy as a whole and especially in peripheral regions. Those processes will accelerate technological convergence of regions and the economy.